Aortic valve perforation following Amplatzer vascular plug device closure of 'pulsatile' Fontan. (December 2017) - Madan, Nitin; Singh, Harinder R.; Mumtaz, Muhammad A.; Gowda, Srinath
Abstract: Persistent antegrade pulmonary blood flow can interfere with optimal functioning of a Fontan circulation in patients with single ventricle physiology. Typically this is addressed surgically at the time of the Fontan procedure with oversewing of the main pulmonary artery, however different variations to this approach have been described. In patients with residual antegrade pulmonary blood flow after a Fontan procedure, "pulsatile" flow into the Fontan system can cause unfavorable hemodynamics leading to various complications. Successful transcatheter device closure of the pulmonary valve in both symptomatic and asymptomatic patients has been described. We report a patient where inadvertent residual antegrade pulmonary blood flow was closed with Amplatzer vascular plug II device with resultant aortic valve perforation noted later in the course requiring surgical removal of the device, aortic valve repair and transection of the main pulmonary artery. Highlights: Persistent antegrade pulmonary blood flow interferes with optimal function of Fontan. Successful transcatheter closure of 'pulsatile' Fontan has been previously described. Aortic valve perforation following Amplatzer vascular plug closure is reported here. The necessity for proper patient selection prior to transcatheter closure is highlighted.